2013
DOI: 10.1016/j.joca.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The matrilin-3 VWA1 domain modulates interleukin-6 release from primary human chondrocytes

Abstract: Based on recombinant expression of different matrilin-3 domains in both monomeric and oligomeric form, this work demonstrated that the VWA1 domain of matrilin-3 is primarily responsible for the induction of IL-6 release and that the oligomerization of the VWA1 domain markedly promotes its activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Matrilin-3 is present at low levels in the joint articular surface and its deposition is upregulated in cartilage and in the synovial fluid of patients with OA as a consequence of cartilage degradation [56][57][58][59][60]. Studies with recombinant MATN3 and human primary chondrocytes have revealed that MATN3 exhibits a context-dependent anabolic or catabolic function by influencing the expression of pro-inflammatory cytokines, ECM degradation enzymes, and ECM synthesis [59,[61][62][63] through the modulation of protein kinase B (AKT) [59], interleukin-6 [62], and interleukin-1 [63,64] signaling pathways. The neoexpression of MATN1 was also observed in the cartilage of OA or rheumatoid arthritis patients [65,66], and MATN2 was recently observed in total knee arthroplasty and suggested as a biomarker for OA [67].…”
Section: Discussionmentioning
confidence: 99%
“…Matrilin-3 is present at low levels in the joint articular surface and its deposition is upregulated in cartilage and in the synovial fluid of patients with OA as a consequence of cartilage degradation [56][57][58][59][60]. Studies with recombinant MATN3 and human primary chondrocytes have revealed that MATN3 exhibits a context-dependent anabolic or catabolic function by influencing the expression of pro-inflammatory cytokines, ECM degradation enzymes, and ECM synthesis [59,[61][62][63] through the modulation of protein kinase B (AKT) [59], interleukin-6 [62], and interleukin-1 [63,64] signaling pathways. The neoexpression of MATN1 was also observed in the cartilage of OA or rheumatoid arthritis patients [65,66], and MATN2 was recently observed in total knee arthroplasty and suggested as a biomarker for OA [67].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, the extracellular matrix has raised more than just a rigid network for cellular attachment. In addition to their function as structural components, Matrilin-3 and Cyclin-I play an important role in cartilage maintenance by improving tissue engineering strategies and targeting the tissue repair (4,16). However, with unknown etiology, TD has been attributed to abnormal chondrocytic differentiation, changes in the activities of matrix metalloproteinase, and changes in genes encoding vascular endothelial growth factor (VEGF) signaling pathways (2,3,20).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that elevated levels of matrilin-3 could in turn increase the expression of ADAMTS4 and ADAMTS5 via IL-1β [ 60 ]. In support of this, Klatt et al [ 61 ] showed that VWFA domains present in matrilin-3 are responsible for IL-6 expression in primary human chondrocytes (See Figure 2 ). Matrilin-3 function shifts from an anabolic to a catabolic effect on ECM components, possibly due to a change from a very low concentration range (100 to 200 ng/mL) to a supra-physiological range (5 to 50 μg/mL).…”
Section: Role Of Matrilin-3mentioning
confidence: 75%